2010
DOI: 10.1021/ja104017y
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based SELDI Probe with Ultrahigh Extraction and Sensitivity for DNA Oligomer

Abstract: We demonstrate that graphene can be used as an ultrahigh efficiency preconcentration and detection platform for ssDNA. DNA-adsorbed graphene can be used directly for Surface Enhanced Laser Desorption Ionization-Time of Flight-Mass Spectrometry (SELDI-TOF-MS). The rapid enrichment of biomolecules and direct, label-free detection are potentially useful for analysis in proteomics and genomics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
200
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(203 citation statements)
references
References 11 publications
0
200
2
Order By: Relevance
“…Previous report suggested that plain GO can strongly bind to single‐strand DNA via π–π stacking whereas the interaction between double‐stranded DNA and GO is relatively weak 21. Thus, we adopted PEI, the “golden standard” cationic polymer in gene transfection for delivery agent.…”
Section: Resultsmentioning
confidence: 99%
“…Previous report suggested that plain GO can strongly bind to single‐strand DNA via π–π stacking whereas the interaction between double‐stranded DNA and GO is relatively weak 21. Thus, we adopted PEI, the “golden standard” cationic polymer in gene transfection for delivery agent.…”
Section: Resultsmentioning
confidence: 99%
“…Derivatives of graphene are considered as useful matrices that can be replaced with organic matrices that are used conventionally for laser desorption-ionization mass spectrometry (LDI-MS), as they are very efficient in absorbing and transferring energy to the analytes [15]. The efficacy of graphene is much higher than that of GO and rGO, because of its electron transfer and high heat dissipation properties [144]. The hydrophobic properties of graphene make the affinity probe of LDI-MS more suitable for analysis of trace amounts of analytes having an aromatic structure which includes proteins [144], ssDNA, small molecules [69] and pollutants [145].…”
Section: Graphene In Mass Spectrometrymentioning
confidence: 99%
“…The efficacy of graphene is much higher than that of GO and rGO, because of its electron transfer and high heat dissipation properties [144]. The hydrophobic properties of graphene make the affinity probe of LDI-MS more suitable for analysis of trace amounts of analytes having an aromatic structure which includes proteins [144], ssDNA, small molecules [69] and pollutants [145]. The unique properties of graphene make it an excellent absorbent in solid-phase extraction.…”
Section: Graphene In Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Use as MALDI matrix is a very interesting application aspect for G. [16][17][18][19][20][21][22][23][24] An ideal MALDI matrix should have strong energy absorption and transfer capability. In this regard, G is a good candidate due to its fast charge carrier mobility [25] and universal and frequency-independent optical absorption properties.…”
mentioning
confidence: 99%